Sistem Pemantauan Tinggi Tanaman Cabai Berbasis Jaringan Menggunakan Modul ESP32-CAM pada Sistem Akuaponik - Juliyan, Muhammad Rafly; PANGARIBUAN, PORMAN; Darlis, Denny (Jurnal Nasional SAINS dan TEKNIK, 2023)
Aquaponics requires special attention in order to get maximum results. Therefore, this research will create a hardware device to monitor the growth of chili plants. Through the camera the height of the chili plants can be measured using image processing. this study the IoT-based chili plant height growth monitoring system uses the ESP-32 CAM in the aquaponic planting model connected via a website can make it easier to monitor the growth of chili plants. In this final project research using ESP-32 CAM as the main component. After testing the monitoring system on chili plants with a height of 12 cm, 23 cm, and 25 cm at a distance of 30. it was found that the ESP-32 CAM can detect the growth of chili plants at a height of 12 cm with an accuracy rate of 97,50% and at 23 cm high with an accuracy rate of 94,58%. And at a distance of 30 cm between the chili plants and the ESP-32 CAM with an accuracy rate of 97,32%. caused the condition of the distance between the camera and the chili plants will affect the process of detecting the size of the chili plants.